SREDNEKEDROVAYA PALEOSEISMODISLOCATION IN THE BAIKAL RIDGE: ITS STRUCTURE AND THROWS ESTIMATED FROM GROUND‐PENETRATING RADAR DATA - O. V. Lunina; A. S. Gladkov; A. A. Gladkov; I. A. Denisenko (Геодинамика и тектонофизика)
Our study aimed to clarify the seismic potential of the Severobaikalsk fault and to discover the structural features of active faults on the NW shores of Lake Baikal. Seismogenic faults and large seismogravitational structures were mapped in the area of the Srednekedrovaya paleoseismodislocation, one of the most remarkable seismotectonic structures in the Baikal region. During the field trip, we tested the capacities of an OKO‐2 georadar and an ABDL‐ Triton antenna used to study cross‐sections of the Baikal ridge. Its slopes are steep, covered with Pinus pumila and abundant screes, many of which developed into boulder streams (‘kurumnik’). The first studies of the Sredneked‐ rovaya paleoseismodislocation were conducted by V.P. Solonenko and his team in 1964–1965. To some extent, this zone can be viewed as a reference object that can provide much information and thus deserves an in‐depth investiga‐ tion using new technologies. Our study combined the field observation and the interpretation of high‐resolution satel‐ lite images provided by DigitalGlobe (US) and downloaded by SAS.Planet. The consolidated database was sufficient for constructing a new schematic map showing the seismogenic faults associated with the Srednekedrovaya paleoseis‐ modislocation. The cumulative length of the ruptures observed on the surface amounted to almost 29.5 km. Some ruptures are separate from each other, and the rupture spacing ranges from the first tens of meters to the first kilome‐ ters. The width of the widest rupture zone is 1.9 km. The length of individual ruptures varies from 5.0 m to 2.7 km. Morphologically, the Srednekedrovaya paleoseismodislocation is represented by ledges and ditches that often comprise complex grabens disturbing the bedrock and slope deposits. The fault structure of this zone is a typical set‐ ting of orthogonal and slightly oblique crustal stretching, but its manifestation differs in the zone segments. In general, it is a combination of steeply dipping and listric faults traced to the depth of 13 m. In plan, the faults are observed to form the systems of subparallel ruptures that mainly strike at 30°. A linear relationship is established between the heights of the seismogenic ledges and the throws estimated from the ground‐penetrating radar data. The former are larger by 0.5–2.0 m than the throw measured from the radargrams. Apparently, this reflects the magnitude of expan‐ sion of the ledge upward along the sloping slope. In the zone of the main fault plane coinciding with the main ledge, the maximum and mean arithmetic throws are 8.3 and 4.93 m, respectively. On other fault planes, the throws range from 0.4 to 4.6 m. The paleoearthquake magnitude ranges from 6.8 to 7.6, according to the estimations from the seis‐ mic rock collapse volume, fault length, and the displacements. Our study of the Srednekedrovaya paleoseismodisloca‐ tion confirms that listric normal faulting is widespread along the western side of the North Baikal basin and gives in‐ direct evidence that conditions for accumulation and release of seismic energy are different on the western and east‐ ern shores of Lake Baikal. It should be noted, however, that in the studied near‐surface layer of the crust, the blocks of loose material may move along the flat planes due to gravitational sliding that increases under the impact of cryogenic processes on the steep slopes of the Baikal ridge.